NAMING OBJECT ON THE BASIS OF NATURAL-GEOGRAPHICAL FEATURES (ACCORDING TO SOUTHERN UZBEKISTAN) - Begimov Odil Tuhtamishovich (Galaxy International Interdisciplinary Research Journal, 2021)
Different lexical and semantic principles are reflected in the naming of geographical objects belonging to the southern region of Uzbekistan. They reflect the naming properties of existing objects depending on the natural-geographical and human practical activities. The article explores issues such as the naming of geographical place names based on natural-geographical features.